IMPLEMENTASI KEBIJAKAN PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 PADA MADRASAH ALIYAH NEGERI 1 PONTIANAK - Ricky Ariani (JPASDEV : Journal of Public Administration and Sociology of Development, 2022)
ABSTRACTThis study aimed to find out the factors that influenced the implementation of online learning during the COVID-19 Pandemic by using an emergent curriculum that began  with online learning to the latest developments in Limited Offline Learning. The research site was Madrasah Aliyah Negeri 1 Pontianak under the guidance of the Regional Office of the Ministry of Religion of Kalimantan Barat Province. This study used the descriptive research method with a qualitative approach until getting an in-depth picture according to the actual method with a qualitative approach until getting an in-depth picture according to the actual conditions or what was in the implementation of online learning which was done by observation techniques, then interviewing so that they could find things that were not disclosed by the informants, lastly, documentation in which the researcher recorded and collected events/information that had passed with recorder and soft-file/hard-file. The results of this study showed that there were four main variables that influenced the implementation of online learning, namely communication, resources, disposition, and bureaucratic structure. In terms of communication, there were differences in the information conveyed by The Madrasah Principal and the teacher, it was also not effective in using e-Learning which was often disconnected due to the network so problems arose during learning. The resources factor  was that the funds/budgets received by the madrasah could be allocated according to their designation to support the learning process for students, especially for internet data so that learning could run well although limited. The disposition factor was the attitude of the implementor that supported the online learning policies. Meanwhile, the bureaucratic structure factor was the current SOP which needed to be reviewed again to adjust to current developments. The researches suggests that soft/hard skills training should be given  to teachers for student character education because currently student character education cannot be implemented and there is a decrease in the level of student discipline and learning innovation, the additional internet data budget should be given for both students and teacher as much as twice than the currently given, and there should be involvement of all parties in SOPs that involved many stakeholders.